Greater jobs in Greater Lagro addressing skills gap through an ICT Incubation Center in Quezon City - Teope, Julia Fatima Yobel C.
Livelihood and economic crises were aggravated due to the COVID-19 pandemic. In the Philippines, a number of workers have been displaced and job applicants have possessed skills that are lost or low-demand. Public and private companies rely on Information and Communications Technology (ICT) skills, which most Filipino workers lack. Although public agencies such as TESDA ( Technical Education And Skills Development Authority) and DICT ( Department of Information and Communications Technology) offer technical and digital courses and training programs, these have been observed to have poor quality operations, limited funds and personnel. There is still a lack of resources pertaining to facilities that collaborate with the Generation Z, technical vocational institutions, and with its local community. Thus, this design project aims to determine and assess architectural strategies in designing an ICT incubation center that serves as an integrated progressive place for collaboration and learning. The study intends to identify the architectural interventions that can address the skills gap particularly, for the Generation Z, the future workforce . The study utilizes a mixed quantitative and qualitative research particularly, reviewing related literature, existing structures and government initiatives, and an online survey for Generation Z. The establishment of a mixed-use ICT Incubation center in the Novaliches-Lagro Growth Area, Quezon City encourages economic activity, upskilling and job opportunities and promotes well-being for the future Filipino workforce. In conclusion, this design project shall shed light on strengthening the labor market programs in the country.